Use of Azacitidine or Decitabine for the Up-Front Setting in Acute Myeloid Leukaemia: A Systematic Review and Meta-Analysis - Miriam Saiz-Rodríguez (MDPI AG, 2021)
Irruption of decitabine and azacitidine has led to profound changes in the upfront management of older acute myeloid leukaemia (AML). However, they have not been directly compared in a randomised clinical trial. In addition, there are no studies comparing the optimal treatment schedule of each drug in AML. A systematic review and meta-analysis on the efficacy of decitabine and azacitidine monotherapy in newly diagnosed AML was conducted. Randomised controlled trials and retrospective studies were included. A total of 2743 patients from 23 cohorts were analysed (10 cohorts of azacitidine and 13 of decitabine). Similar response rates were observed for azacitidine (38%, 95% CI: 30–47%) compared to decitabine (40%, 95% CI: 32–48%) (p = 0.825). Overall survival (OS) between azacitidine (10.04 months, 95% CI: 8.36–11.72) and decitabine (8.79 months, 95% CI: 7.62–9.96) was also similar (p = 0.386). Patients treated with azacitidine showed a lower median OS when azacitidine was administered for 5 days (6.28 months, 95% CI: 4.23–8.32) compared to the standard 7-day schedule (10.83 months, 95% CI: 9.07–12.59, p = 0.002). Among patients treated with decitabine, response rates and OS were not significantly different between 5-day and 10-day decitabine regimens. Despite heterogeneity between studies, we found no differences in response rates and OS in AML patients treated with azacitidine or decitabine.